MODELLING THE BENCHMARK SPOT CURVE FOR THE SERBIAN MARKET - Drenovak, Mikica; Urošević, Branko (Economic Annals, 2010)
The objective of this paper is to estimate Serbian benchmark spot curves using the Svensson parametric model. The main challenges that we tackle are: sparse data, different currency denominations of short and longer term maturities, and infrequent transactions in the short-term market segment vs daily traded medium and long-term market segment. We find that the model is flexible enough to account for most of the data variability. The model parameters are interpreted in economic terms.